EFEKTIFITAS PIJAT OKSITOSIN TERHADAP INVOLUSI UTERI DAN PRODUKSI ASI PADA IBU POST PARTUM DI KECAMATAN KALIWUNGU KABUPATEN KENDAL - sri rahayu; aris sugiarto (Universitas Muhammadiyah Kudus, 2018)
Abstract Bleeding is a cause of maternal mortality in Indonesia. Several efforts have been done to decrease maternal mortality, one of them is maternity counseling program (continuty of care/CoC model) in Central Java province. Post partum bleeding can be prevented by giving oxytocin, in a form of oral intranasal, intramuscular and with oxytocin massage to stimulate oxytocin hormone. Oxytocin hormone may elicit uterine contraction and help to increase breast milk production. The purpose of the research is to ascertain the effectiveness of oxytocin massage towards uteri involution and breast milk production of post partum mother. This research uses quasi experiment method with 43 mothers given the treatment and 43 post partum mothers as control. Some of breast milk production respondents who were given massage treatment show enhancement proven by weight gain from birth weight. While uteri involution shows respondents in control group experiencing abnormal involution (37,2 %) and the rests experiencing normal involution, whilst intervention group shows normal involution process (62,8%) and the rests experiencing abnormal involution process which proven by the decline of Fundus height as well as the theory. It is found that post partum mothers who were given intervention, experiencing normal uteri involution and increasing breast milk production so they can breastfeed exclusively. Key words: Oxytocin massage, uteri involution, breast milk production, post partum mother